A case study of feedback strategies in The Open Learning Systems Trust (OLSET) Radio Learning Programmes - Kenyon, Jennifer Berry (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 1999)
The following is a case study of three Foundation Phase teachers' classroom practice while using the Open Learning Systems Education Trust (OLSET) Radio Learning Programmes, "English In Action" Level Two materials with their Grade Two learners. This case study describes and analyses the feedback strategies of the three teachers. The radio learning programmes have been developed to provide teachers with an effective interactive set of materials to assist their learners in the acquisition of English. These audio materials also provide teachers with opportunities to be creative and responsive to their learners' specific needs. The feedback strategies described in this study are the teachers' use of their learners' mother tongue, correction oflearner error, and use of praise and encouragement during the three Teacher-Led Activity (TLA) segments of the radio programmes. These TLAs give teachers approximately 12 minutes per lesson during which they are called on to manage the materials according to their learners' specific needs. The TLAs are specifically designed to give learners the opportunity to use and respond to English in particular contexts. This study examines three teachers' feedback to their learners in order to find out what kind of feedback has been made. An attempt has also been made to analyse the nature of the feedback. It was found, from the description and analysis of the teachers' feedback, that when teachers used their learners' mother tongue this was more often used to translate words or phrases which were part of the radio narrator's instructions to the learners and these translations were then repeated in English. Teachers corrected very few learner errors. The most common form of correction was to model the correct form and have the learners repeat this. In spite of claiming that correction of errors was important and all three teachers said they did correct their learners' errors, there was very little evidence of this practice in the sample described in this study. The use of praise and encouragement was a strategy that all three teachers claimed they practised but almost no instances of the use of praise were described. The three teachers used only the word "good" to praise any of their learners' efforts and, in fact, all three used this only twice in each of the three lessons described in this study. In terms of language learning a number of factors have been compared. Some of these include teachers' repetition oflearners' answers and their correction oflearner responses by modelling. They were also observed allowing a variety of learner response as well as ensuring a number of individual learners were able to respond. These factors appear to have enhanced the language learning in the classrooms. However, it was also observed that the teachers needed more support in order to develop more explicit strategies to use their learners' mother tongue, to praise learners and to correct learner error purposefully in their classroom practice. There is a need for guidance to be given teachers in the development and use of open-ended questions and strategies which could encourage the development of higher order language skills in their learners. These findings will influence OLSET's teacher development curriculum. It is envisaged that strategies and activities designed to provide teachers with opportunities to reflect on their own practice with regard to the feedback they provide will be incorporated into the workshops and teacher support systems provided by OLSET's teacher development team.
Keywords: English language -- Study and teaching -- Foreign speakers; Educational broadcasting; Radio in education -- South Africa